Pengembangan Pembelajaran Pendidikan Kesehatan Melalui Personal Health Card Assignments Untuk Peserta Didik Sekolah Menengah Atas (Indonesian Journal for Physical Education and Sport, 2021)
The purpose of this research is to produce teaching material products as a guide that can optimize the health education learning materials through personal health card assignments. The research method in this study is qualitative. Sample in this study were students at Pegandon High School, 1st Kendal High School and 2nd Kendal High School. The results of the study obtained an evaluation of health education experts with an average percentage of 71% in the "good" category. While the field trial gets results:1) Physical education teacher of Pegandon High School got 92.8%, 2) Physical Education Teacher of 1st Kendal High School got 95%, 3) Physical Education Teacher of 2nd Kendal High School received a percentage by 99%. With an average percentage of 93.4%. The conclusions based on research that personal health card assignments for high school students are appropriate for students to use in the process of learning health material. The author's suggestion is for the physical education teacher to start to use this personal health card assignment as an alternative in delivering health education material in class.